Examination of the Relationship among Death Anxiety, Spirituality, Religious Orientation and Existential Anxiety - Merve Halıcı Kurtulan; Özlem Karaırmak (Spiritual Psychology and Counseling)
In this study, the associations among death anxiety, spiritual tendencies, existential anxiety, and religious tendencies were examined. In addition, this study investigated whether these variables changed with respect to demographic characteristics. The study group was composed of 404 university students. Data was collected by administering the personal demographic form, Death Anxiety Scale, Existential Scale, Religious Tendency Scale, and Spirituality Scale. In line with the purpose of the study, the relational screening model and descriptive methods have been used and participants are identified as study groups. Male participants scored significantly higher than female participants. Gender was not found to have an effect on the other variables. Existential anxiety did not differ within groups with respect to having a religious education. Participants who had received a religious education had higher death anxiety and less spiritual tendencies. Motivation for religious tendencies was found to be external. According to the results, death anxiety and existential anxiety are negatively correlated; existential anxiety and spiritual tendencies are positively correlated; and religious tendencies, which have externally motivations, and spiritual tendencies are negatively correlated. Death anxiety, spiritual tendencies, and religious tendencies predict existential anxiety. As suggestions, the number of studies that examine the associations among existential anxiety, religious tendencies, and spiritual tendencies should be increased, and the quality of religious education should be discussed in detail.